Experimental and numerical study of a hybrid solar-combustor system for energy efficiency increasing. (1st March 2020) - Sirignano, Mariano; De Falco, Gianluigi; Commodo, Mario; Minutolo, Patrizia; Tregambi, Claudio; Solimene, Roberto; Salatino, Piero
Abstract: Coupling of traditional combustion technologies with solar thermal energy is fundamental to enlarge the field of applicability and to lower the costs of renewable energy sources. A possible solution is represented by direct irradiation of a flame with concentrated solar energy, so as to increase its temperature thanks to the high absorption coefficient of combustion by-products such as soot particles. In this study, we use a detailed model of soot formation and oxidation to simulate the behaviour of a coflowing diffusion ethylene flame with and without the exposure to a concentrated solar radiation. Modelling data are compared with experimental data reported in the literature. Results confirm that our model is able to reproduce the effect of radiation both matching the temperature and soot volume fraction increase. Successively, a modified version of the solar-combustion hybrid system has been setup to test the effect of solar light orientation on the combustion process. A simulator of concentrated solar energy has been used to directly irradiate the flame from the top. Thermocouple-based temperature measurements highlighted that the flame effectively absorbed solar radiation.